Prevalence of Multidrug-Resistant Salmonella enterica Serovars in Buffalo Meat in Egypt - Samir Mohammed Abd-Elghany; Takwa Mohammed Fathy; Amira Ibrahim Zakaria; Kálmán Imre; Adriana Morar; Viorel Herman; Raul Pașcalău; Laura Șmuleac; Doru Morar; Mirela Imre; Khalid Ibrahim Sallam (Foods, 2022)
The current study aimed to investigate the presence of Salmonella spp. prevalence in buffalo meat in Egypt, along with studying the antimicrobial susceptibility of the recovered isolates. Salmonella spp. was detected in 25% of tested buffalo meat. A total of 53 (100%) isolates were genetically verified by PCR as Salmonella, based on the detection of the invA gene. The stn and hilA genes were detected in 71.7% (38/53), and 83.0% (44/53) of the recovered isolates, respectively. Salmonella Enteritidis (11/53; 20.7%) was the most commonly isolated serovar, followed by S. Typhimurium (9/53; 17%), S. Montevideo (6/53; 11.3%), meanwhile, S. Chester, S. Derby, S. Papuana, and S. Saintpaul were the least commonly identified serovars (a single strain for each; 1.9%). Among the 16 antimicrobials tested, amikacin, imipenem, gentamicin, cefotaxime, meropenem, ciprofloxacin, and enrofloxacin were the most effective drugs, with bacterial susceptibility percentages of 98.1%, 94.3%, 92.5%, 86.8%, 83.0%, 73.6%, and 69.8%, respectively. Meanwhile, the least effective ones were erythromycin, streptomycin, clindamycin, cefepime, and nalidixic acid, with bacterial resistance percentages of 100%, 98.1%, 88.7%, 77.4%, and 66%, respectively. Interestingly, the high contamination level of Egyptian buffalo meat with multidrug-resistant Salmonella (79.2%; 42/53) can constitute a problem for public health. Therefore, programs to control Salmonella contamination are needed in Egypt.